FEMINISME RADIKAL DALAM NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM KARYA DIAN PURNOMO DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Juliana, Rini (Universitas Indraprasta PGRI, 2023)
The purpose of this research is to describe the forms of radical feminism in the novel Perempuan Yang Menangis kepada Bulan Hitam by Dian Purnomo. This research uses the theory of radical feminism sourced from Tong in his book entitled Feminist Thought and its implications for Indonesian language learning class XII at the Senior High School (SMA) level. The method used in this research is descriptive qualitative which results in the form of words and narratives that describe the events experienced by female characters in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian purnomo. Based on the results of research in the novel Perempuan Yang Menangis kepada Bulan Hitam by Dian Purnomo, there are forms of radical feminism, such as 1) social discrimination experienced by women, 2) sexual harassment committed by men, 3) sexual violence committed by men, 4) exploitation of women by families and men against women in Sumba, East Nusa Tenggara caused by ancestral cultural heritage, such as kawin tangkap.